2024 Standardization of Polysomnography Reports - A Consensus of the Brazilian Sleep Association - Palombini, Luciana de Oliveira; Mello, Luciane Impellizieri Luna de; Santos-Silva, Rogerio; Assis, Marcia; Cunha, Thays Crosara Abrahao; Drager, Luciano Ferreira; Zancanella, Edilson; Alves, Rosana Cardoso; Bacelar, Andrea; Bagnato, Mauricio da Cunha; Balsalobre, Rafael de Andrade; Bianchini, Esther Mandelbaum Goncalves; et al. (Thieme Medical Publ Inc, 2024)
Introduction The absence of standardized reporting for sleep medicine exams across different laboratories can lead to misinterpretation, diagnostic inconsistencies, and suboptimal treatment strategies. This document seeks to establish guidelines for the development of sleep study reports, covering recordings from studies of types 1 to 4, and represents the official position of Associa & ccedil;& atilde;o Brasileira do Sono (ABS; Brazilian Sleep Association) on the standardization of polysomnography (PSG) and cardiorespiratory polygraphies. Materials and Methods The recommendations for the items to be reported in PSG records were developed by means of a Delphi study, comprised of two voting rounds. In each round, participants had to vote regarding the appropriateness of items to be reported in type-1 to -4 sleep studies, rating them as recommended , optional , or not recommended . The consensus threshold was set at 66% in each voting round, or 75% for the combined responses of recommended and optional . Results The panel was comprised of 29 experts. After 2 voting rounds and subsequent deliberations by the steering committee, 352 items were included in the final set of recommendations. Consensus was achieved for 339 items (96.3%), of which 145 (41.2%) were classified as recommended , 154 as optional (43.8%), 35 as not recommended (9.9%), and 5 as not allowed (1.4%). No consensus was reached for 13 items (3.7%). The items recommended in this consensus are detailed in the main text. Conclusion These guidelines provide comprehensive recommendations for reporting diagnostic tests in sleep medicine.
Keywords: Delphi; diagnosis; polysomnography; sleep apnea